A Comparative Study of delivery and Its Role in Sale Contract of Movable property in Iranian and British Law (with Emphasis on Production Items of Handicraft Artisans) - Soudabeh Dehghani; Mohammad Javad Saffar; Hamidreza Alikarami (هنر اسلامی, 2023)
The purpose of concluding any contract is to implement its amount and to be bound by the effects of that contract. The contract of sale, as the most obvious examples of the necessary sale, in order to be on the path of its implementation, must have clear provisions and the parties must not have a dispute over the terms of validity and the terms of the contract and how to implement it. One of these conditions is submission. In principle, a contract is realized without surrender, except in the case of an irreplaceable contract and some exceptional contracts. However, in all cases, the contract and surrender are mutually related. Is given. Surrender and receipt is not a legal act because it is not a condition for obtaining the seller's permission. The need to determine the case does not make surrender a legal act. This study aims to explain the category of submission in the contract of sale and its conditions in the two legal systems of Iran and the United Kingdom.